Succeeding at work [ - Vallis, Adrian (I want that job!program 5, 2000)
A new job can be an exciting opportunity and this program helps prepare you to make the most of it. Topics include workplace culture, what your employer will expect from you, what you should expect from your employer including payslips and superannuation, working conditions and how to deal with discrimination, harassment and violence. The video provides a case study of Mike who has just accepted his first full time job